IMPROVING STUDENTS’ READING COMPREHENSION OF RECOUNT TEXT THROUGH QUESTION ANSWER RELATIONSHIP STRATEGY - Rahmawati, Ridha; Rufinus, Albert; Salam, Urai (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: This research intended to improve students’ reading comprehension of recount text through Question Answer Relationship (QAR) strategy on the eighth grade students of SMP Haebat Islam Gontong Kubu Raya. The research method that used was Classroom Action Research (CAR) which consists of three cycles. To measure the students’ improvement on reading comprehension, the writer administered the evaluation test. The research finding showed that QAR strategy improved students’ reading comprehension. Based on the analysis of the students’ test result, QAR strategy made students achievement improved in every cycle. In the first cycle, the students still had difficulty in comprehending the recount text, both text explicit and text implicit information. Students’ mean score was 61.17. In the second cycle, students’ ability in identify text explicit information was better compared to the previous cycle, their ability in answer Right There questions improved. Students’ mean score was 77.5. In the third cycle, the students made significant improvement in comprehending text implicit information. It showed by students’ ability in answer the Think & Search questions improved. The students’ mean score was 83.33 which categorized as good to excellent. Key words: reading comprehension, QAR strategy, classroom action research. Abstrak: penelitian ini bertujuan untuk memperbaiki pemahaman membaca teks recount dengan menggunakan strategi Question Answer Relationship (QAR) pada siswa SMP Hebat Islam Gontong Kubu Raya kelas delapan. Metode penelitian yang digunakan adalah penelitian tindakan kelas yang terdiri atas tiga siklus. Berdasarkan analisis terhadap hasil tes siswa, strategi QAR membuat pencapaian siswa meningkat dalam tiap siklus. Pada siklus pertama, banyak siswa masih kesulitan untuk memahami baik informasi eksplisit maupun implisit. Nilai rata-rata siswa adalah 61.17. Pada siklus kedua, kemampuan siswa dalam mengidentifikasi informasi eksplisit lebih baik dibandingkan dengan siklus sebelumnya. Nilai rata-rata siswa adalah 77.5. Pada siklus ketiga, kemampuan siswa dalam menjawab pertanyaan Think and Search meningkat. Siswa membuat peningkatan yang signifikan dalam memahami informasi implisit. Nilai rata-rata siswa adalah 83.33 yang dikategorikan sebagai good to excellent. Kata kunci: pemahaman membaca, strategi QAR, penelitian tindakan kelas